Advertisement Remove all ads

Multiplication of Algebraic Expressions - Multiplying a Monomial by a Trinomial

Advertisement Remove all ads

Topics

notes

Multiplying a Monomial by a Trinomial:

  • We commonly use distributive law in our calculations.

  • Multiply each term of the trinomial by the monomial and add products.

1) Multiply 4y(3y2 + 5y – 7)

= 4y(3y2 + 5y – 7)

= (4y × 3y2) + (4y × 5y) + (4y × (-7))

= 12y3 + 20y2 – 28y.

2) Multiply 2(y3 – 4y2 + 5)

= 2(y3 – 4y2 + 5)

= 2y3 + 2 × (- 4y2) + 2 × 5

= 2y3 – 8y2 + 10.

3) Multiply 3p × (4p2 + 5p + 7)

= 3p × (4p2 + 5p + 7)

= (3p × 4p2) + (3p × 5p) + (3p × 7)

= 12p3 + 15p2 + 21p.

If you would like to contribute notes or other learning material, please submit them using the button below.

Shaalaa.com | How to Multiply a Monomial by a Trinomial?

Shaalaa.com


Next video


Shaalaa.com


How to Multiply a Monomial by a Trinomial? [00:12:23]
S
Series: Multiplying a Monomial by a Trinomial
0%


Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×